Migration, memory, and diversity : Germany from 1945 to the present - Wilhelm, Cornelia, 1964- (New York : Berghahn Books, 2017)
"Within Germany, policies and cultural attitudes toward migrants have been profoundly shaped by the difficult legacies of the Second World War and its aftermath. This wide-ranging volume explores the complex history of migration and diversity in Germany from 1945 to today, showing how conceptions of 'otherness' developed while memories of the Nazi era were still fresh, and identifying the continuities and transformations they exhibited through the Cold War and reunification. It provides invaluable context for understanding contemporary Germany's unique role within regional politics at a time when an unprecedented influx of immigrants and refugees present the European community with a significant challenge"--Publisher description.
Preface / Konrad H. Jarausch -- Introduction / Cornelia Wilhelm -- Part I. Postwar migrations : history, memory, and diversity -- The commemoration of forced migrations in Germany / Martin Schulze-Wessel -- A missing narrative : displaced persons in the history of postwar West Germany / Anna Holian -- Inclusion and exclusion of immigrants and the politics of labeling : thinking beyond "guest workers," "ethnic German resettlers," "refugees of the European crisis," and "poverty migration" / Asiye Kaya -- Refugee reports : asylum and mass media in divided Germany during the Cold War and beyond / Patrice G. Poutrus -- Part II. Institutional responses to migration and cultural difference -- History, memory, and symbolic boundaries in the Federal Republic of Germany : migrants and migration in school history textbooks / Simone Lassig -- Representations of immigration and emigration in Germany's historic museums / Katharzyna Nogueira and Dietmar Osses -- Archival collections and the study of migration / Klaus A. Lankheit -- Thinking difference in postwar Germany : some epistemological obstacles around "race" / Rita Chin -- Part III. Reconsidering history, memory, and identity in the post-Unification period -- Nationalism and citizenship during the passage from the postwar to the post-postwar / Dietmar Schirmer -- Learning to live with the other Germany in the post-Wall Federal Republic / Kathrin Bower -- Conflicting memories, conflicting identities : Russian-Jewish immigration and the image of a new German Jewry / Karen Korber -- Swept under the rug : home-grown anti-semitism and migrants as "obstacles" in German Holocaust remembrance / Annette Seidel-Arpaci.
Includes bibliographical references and index.
Description based on print version record.
eBooks on EBSCOhost
Keywords: Germany -- Emigration and immigration -- Social aspects; Immigrants -- Germany -- Social conditions; Refugees -- Germany -- Social conditions; Minorities -- Germany -- Social conditions; World War, 1939-1945 -- Influence; Memory -- Social aspects -- Germany; Cultural pluralism -- Germany; Multiculturalism -- Germany; Difference (Psychology) -- Social aspects -- Germany; Germany -- Ethnic relations; Allemagne -- Émigration et immigration -- Aspect social; Minorités -- Allemagne -- Conditions sociales; Guerre mondiale, 1939-1945 -- Influence; Diversité culturelle -- Allemagne; Multiculturalisme -- Allemagne; Psychologie différentielle -- Aspect social -- Allemagne; SOCIAL SCIENCE -- Emigration & Immigration; SOCIAL SCIENCE / Emigration & Immigration; Cultural pluralism; Difference (Psychology) -- Social aspects; Emigration and immigration -- Social aspects; Ethnic relations; Immigrants -- Social conditions; Influence (Literary, artistic, etc.); Memory -- Social aspects; Minorities -- Social conditions; Multiculturalism; Refugees -- Social conditions; Germany; 1939-1945